UNWRITTEN POLICY, CONTRADICTION OR ACCEPTANCE IN TURKISH SOCIETY VIEWED FROM A RELIGIOUS LIFE PRESPECTIVE - Anggraeni, Nur Najmi; SOYDAN, Mustafa Zafer; Ustaadza, Lailatus Sholikhah; Setiawan, Refly; Melinda, Esti (The Ministry of Religious Affairs, The Republic of Indonesia, 2023)
Majority of Turkish society adheres to the Sunni Islamic faith, while the Alevi group has emerged with a different faith. The Alevi are a complex and diverse religious and cultural identity that has undergone numerous changes in its position, outlook and interactions with the rest of Turkish society. Turkish society is not static, the contradictory attitudes taken by Turkish society towards the Alevi community, and the shifting perspectives on Alevi religious life, are often questioned. Their society changes over time due to factors such as political developments, generations and social movements. By 2022, 25 million Alevi people in Turkey will have no legal security. Alevis have faced challenges such as discrimination, unequal treatment and lack of recognition for their unique religious practices. This raises the issue of the Turkish government’s policy in dealing with the problems of the Alevi community, the attitude of Turkish society in dealing with the contradictions of the Alevi community, and the comparison of Alevi beliefs with the beliefs of Turkish society and the impact of Alevi groups on Turkish society. This paper uses a descriptive qualitative research method with data analysis and literature review. The findings of this study are that the Turkish government does not have a structured and official policy on the acceptance or rejection of the Alevi community, and Turkish society is beginning to open up to the understanding of Alevi culture. Despite the differences between Sunni and Alevi Islam, Alevi community is still able to perform their rituals without any hindrance.